DIDACTIC ROLE OF CHANG AND QANON INSTRUMENTS IN UZBEKISTAN MUSICAL HERITAGE (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role of the chang and qon instruments in the Uzbek musical heritage, their didactic functions in the educational process, and their importance in educating young performers. It also highlights the effectiveness of methodological approaches and practical exercises used in studying these instruments.